2020
DOI: 10.1007/s41207-020-00180-0
|View full text |Cite
|
Sign up to set email alerts
|

Application of life-cycle assessment to the eco-design of LED lighting products

Abstract: An approach for integrating life-cycle assessment (LCA) into the eco-design of lighting products was developed, and LCAs of five lighting products that are currently on the market were then carried out using this approach. Based on the results of these LCAs, the sustainability requests for lighting products were derived and embedded into the product design specification (PDS), thus ensuring that any product developed according to the PDS would have the desired eco-design features. A new sustainable lighting pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…This plays a significant role in product innovation from an ecological perspective [37]. In their study, the authors of [38] assessed five interior LED lighting products using screening techniques to identify the problems and opportunities of integrating LCA in LED lighting eco-design. K. Miettunen et al [39] and I. Kazancoglu et al [40] stated that recycling should be a critical part of a holistic eco-design.…”
Section: Learning-lmentioning
confidence: 99%
“…This plays a significant role in product innovation from an ecological perspective [37]. In their study, the authors of [38] assessed five interior LED lighting products using screening techniques to identify the problems and opportunities of integrating LCA in LED lighting eco-design. K. Miettunen et al [39] and I. Kazancoglu et al [40] stated that recycling should be a critical part of a holistic eco-design.…”
Section: Learning-lmentioning
confidence: 99%
“…Although numerous studies addressed the environmental aspects of lighting products ( Tähkämö et al, 2012 ;Principi and Fioretti, 2014 ;Wang et al, 2020 ), they compared the environmental impacts and energy efficiencies of different technologies of LED lighting products. However, only a few researchers considered the product development and service in terms of the combined impacts of environmental, social, and economic aspects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although the PDS method has been utilised in product design for many years, the incorporation of ecoconstrains in the PDS has not been given enough attention, such as those [14][15][16][17] cited in the PDS literature review given in the introduction section. The existing research found in the literature, such as those [18][19][20][21] reviewed in the introduction section, focuses in particular on some aspects of the environmental impact of the lighting products, such as energy consumption, eco-efficiency, eco-cost and LCA. None of them considered the full list of eco-PDS.…”
Section: Eco-design Aims With Related Issuesmentioning
confidence: 99%
“…Klaassen,et al [20] investigated the eco-efficient value creation of residential street lighting systems by simultaneously analysing the value, costs and eco-costs during the design and engineering phase. Wang, et al [21] conducted the life cycle assessment of five domestic lighting products existing in the market, and, based on the assessment results, a new sustainable lamp was developed. Richter, Tähkämö and Dalhammar [22] investigated the trade-offs with longer lifetimes of LED lamps considering product development and energy contexts.…”
Section: Introductionmentioning
confidence: 99%